Symposium 4: Quantitative and Qualitative Research: Conflicting Paradigms or Perfect Partners? - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2004)
This paper will examine the use of quantitative and qualitative methods as complementary research methods. It asks the fundamental question whether these two approaches can be used jointly in a principled manner. The pressure in educational research has been towards using the two methods alongside each other. In applied research the use of the two approaches in the same project is accepted yet we still find serious objections raised to such work when it is presented in a more formal context. Evaluation studies are often multi-method in their approaches whilst doctoral students will still find examiners balking at the use of mixed methods in doctoral research. This paper tries to both investigate the source and nature of this division and to illustrate practical ways in which the division may be overcome.